IMPACT OF CHRONIC GAMMA-IRRADIATION ON THE LITTER DECAY OF A MIXED MEDITERRANEAN FOREST IN CADARACHE - FRANCE MICROARTHROPODS RESPONSE (PEDOBIOLOGIA, 1995)
An area of mixed forest containing white oak (Quercus pubescens W.) and evergreen oak (Quercus ilex L.) in Cadarache has been irradiated for 16 years, since 1969, by a 137 cesium source of 31.45 TBq. Mass loss of experimental litter over a period of 22 months and its recolonization by soil microarthropods was studied at five stations receiving decreasing radiation levels (100 mGy/h(-1) to 0.3 mGy/h(-1)) and in a control area. At the end of the experimentation, the mass loss of the litter was substantially lower in the three most irradiated stations. Additionally recolonization of litter by microarthropods was low in these three stations compared with the three others. Population density of Oribatids, `'other Acarina'', Collembola and various Arthropods, was considerably lower. These results were dependant upon direct and indirect consequences of irradiation on the ecosystem. Destruction of trees and shrubs in the most irradiated areas (100-60 mGy/h(-1)) did in fact lead to the reduction of soil moisture and an absence of organic matter input. Microflora could not develop and insufficient trophic resources did not allow for recolonization by fauna, which in turn slowed down the eventual disappearance of the litter.